ACTION OF SHAKEN SERUM ON HOMOLOGOUS FIBROBLASTS - Carrel, Alexis (The Rockefeller University Press, 1922)
The preceding experiments showed that partial or complete inactivation of serum by shaking brought about a marked decrease in the activity of homologous fibroblasts. Generally, serum was not completely inactivated by shaking. In only one instance was the hemo-lytic effect of chicken serum on sheep corpuscles entirely lost after the serum had been shaken for 8 hours. In all other cases, the normal hemolytic power of chicken and dog sera for sheep erythrocytes was merely decreased. The effect of shaking varied according to certain conditions of the serum. It may be compared to the inffuence of heat, which differs widely according to individual sera, even when they are obtained from animals which are apparently in identical condition. Shaken serum always inhibited the activity of homologous fibroblasts more than normal serum. When chicken serum was completely inactivated by shaking, its restraining action on chicken fibroblasts became also more marked. On the contrary, dog serum partly inactivated by shaking was much less toxic for chicken fibroblasts than normal serum. Thus, shaking brought about a change in the condition of serum, against which homologous and heterologous fibroblasts reacted in an opposite manner. At the same time, the normal lytic action of serum on foreign erythrocytes decreased. This last phenomenon is caused, as is well known, by the partial or complete destruction of alexin. The decrease of the restraining effect of shaken serum on foreign fibroblasts may be attributed to the same cause. The increase of the inhibiting action of shaken serum on homologous fibroblasts is due possibly to the disappearance of a substance favoring the activity of homologous cells. A similar hypothesis was advanced for explaining the increase of the growth-inhibiting action of serum under the influence of senescence and of heat. The restraining power of adult serum on cell multiplication may be due to the antagonistic action of growth-promoting and growth-inhibiting substances, the growth-promoting substance being as unstable as alexin and certain tissue juices which have the property of increasing the rate of cell proliferation. Alexin and growth-activating substances contained in embryonic and gland tissue juices have in common the property of being destroyed by heat and by shaking. Leucocytes added to serum under certain conditions increase its hemolytic power on foreign erythrocytes and decrease its inhibiting action on homologous fibroblasts. Variations in the alex-inic activity of serum under other influences are followed also by a change in its action on homologous cells. Long ago, Gengou found that serum from plasma is less bactericidal than serum from blood. We observed that the lytic effect on sheep erythrocytes of dog and chicken serum from blood was sometimes more marked than that of serum from plasma, but there was often no difference in the action of both sera. At the same time, the growth of homologous fibroblasts was always more extensive in the serum from blood. The opposite effect was observed when heterologous fibroblasts were used. The growth-inhibiting power of serum from blood was still less marked on leucocytes than on fibroblasts. But embryonic juice, which greatly enhances the rate of multiplication of homologous cells, did not increase the lytic action of serum on foreign erythrocytes. It may be concluded that, under the conditions of the experiments: 1. Chicken serum partly or completely inactivated by shaking becomes more inhibiting for chicken fibroblasts. 2. Dog serum partly inactivated by shaking becomes less inhibiting for chicken fibroblasts.